Inhibition of Cardiac Hypertrophy Effects in D-Galactose-Induced Senescent Hearts by Alpinate Oxyphyllae Fructus Treatment. (5th April 2017) - Chang, Yung-Ming; Chang, Hen-Hong; Lin, Hung-Jen; Tsai, Chin-Chuan; Tsai, Chuan-Te; Chang, Hsin-Nung; Lin, Shu-Luan; PadmaViswanadha, Vijaya; Chen, Ray-Jade; Huang, Chih-Yang
Abstract : Aging is a complex physiological phenomenon accelerated by ROS accumulation, with multisystem decline and increasing vulnerability to degenerative diseases and death. Cardiac hypertrophy is a key pathophysiological component that accompanies the aging process. Alpinate Oxyphyllae Fructus ( Alpinia oxyphylla MIQ, AOF) is a traditional Chinese medicine, which provides cardioprotective activity against aging, hypertension, and cerebrovascular disorders. In this study, we found the protective effect of AOF against cardiac hypertrophy in D-galactose-induced aging rat model. The results showed that treating rats with D-galactose resulted in pathological hypertrophy as evident from the morphology change, increased left ventricular weight/whole heart weight, and expression of hypertrophy-related markers (MYH7 and BNP). Both concentric and eccentric cardiac hypertrophy signaling proteins were upregulated in aging rat model. However, these pathological changes were significantly improved in AOF treated group (AM and AH) in a dose-dependent manner. AOF negatively modulated D-galactose-induced cardiac hypertrophy signaling mechanism to attenuate ventricular hypertrophy. These enhanced cardioprotective activities following oral administration of AOF reflect the potential use of AOF for antiaging treatments.